Ar bulk diffusivity experiments in microgabbros with implications for the Venusian geodynamics - Semêdo, Pedro de Almeida (2022)
The argon geochemical system is an important tool for the planetary sciences. 40Ar is radiogenic and produced by the radioactive decay of 40K (half-life ~ 1.25 Ga) in minerals in the crust and mantle of rocky planets, while 36Ar and 38Ar are primordial. The atmospheres of Earth and Venus share similar 36Ar/38Ar ratios (5.3 and 5.5, respectively) but contrasting 40Ar/36Ar ratios (~300 vs. 1, respectively), indicating that Earth is more effective in degassing 40Ar. Because volcanism is a major 40Ar degassing agent, these data suggest higher volcanic activity through Earths evolution relative to Venus. However, diffusion is another possible 40Ar transporter from geospheres to atmospheres and the average surface temperature on Venus (460 ºC) is above the closure temperature of the gas in most silicate systems. Because there is no data concerning the diffusion of Ar in basaltic rocks, here, bulk diffusion experiments were made using synthetic microgabbros (similar to Venusian basalts) under 460 ºC (1 atm) to investigate the effectiveness of diffusion in mobilizing Ar in the crust of Venus. A vertical tubular furnace (VTF) was used to melt and crystallize a tholeiitic basalt powder under Ar saturation conditions to dope the aliquots with the gas, generating a total of ten Ar-saturated microgabbro beads. Eight of these beads were reintroduced into the VTF (100% CO2 atmosphere) and muffle furnace (MF, air composition) simultaneously (4 in each furnace) at 460ºC. The two furnace apparatuses were used to check if the atmospheric composition would alter the results. Aliquots were then removed after 2, 4, 8, and 16 days. Bulk diffusion coefficients (Dbulk) were obtained by analyzing the variation of Ar concentration in the beads after the experiments. Experiments held in the VTF and MF had similar results. Two different solutions for the diffusion equation were used, with the best results showing Dbulk values of ~ 3.5 x 10-13 m²/s. The results indicate that diffusion is very slow in the analyzed conditions and that less than 1 % of the total Ar would have been removed from the Venusian crust if diffusion was the only degassing agent. Thus, the data support the idea that volcanism is the main source 40Ar to the atmosphere in anhydrous crusts and that, indeed, Earth must have had higher volcanic activity in its history in comparison to Venus. Finally, I suggest that the crust of Venus has an excess of 40Ar and that the planets atmospheric 40Ar/36Ar ratio should become more similar to Earths after the next global resurfacing event, when magma should be in direct contact with the atmosphere, favoring the degassing of 40Ar.